PENGARUH MEDIA EXPOSURE, PROFITABILITAS TERHADAP CORPORATE RESPONSIBILITY - Didan, Didan Hilmy Fakhrian (CV. Denasya Smart Publisher, 2024)
This research aims to identify and analyze the influence of media exposure and profitability on corporate social responsibility (CSR). By using panel data regression analysis on the annual reports of companies listed on the Indonesia Stock Exchange (BEI), it was found that profitability, measured by Return on Assets (ROA), has a significant influence on CSR expenditure. Companies with high levels of profitability tend to allocate more funds to CSR activities, indicating a greater ability and drive to invest in sustainability and social responsibility. Media exposure is also considered an important factor influencing a company's perception and response to CSR. This research underscores the importance of corporate governance, internal controls, the role of auditors, and compliance with accounting standards in ensuring the integrity of financial reports, which is important for stakeholder decisions and preventing financial scandals. The results are expected to make a significant contribution to improving the integrity of financial reports and advancing better CSR practices in the future.